Qualidade de vida de professores do município de Santarém (Pará) que foram aco-metidos pela COVID-19. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The COVID-19 pandemic has reached major proportions in Brazil and has impacted the country in several ways, with rapid spread and various repercussions, in addition to the multi-organ ones caused by the virus itself, it has interfered in several spheres, including education. After falling ill, a considerable portion of the population has been showing symptoms, some still similar to those of the disease and others new. The evidence points to a post-COVID-19 syndrome and the possibility of worsening of symptoms already reported by some patients. In fact, it is still difficult to measure the impact that the pandemic has left behind, but it is important to investigate the state of health of the population after such a critical period experienced around the world and to investigate whether people have already managed to return to "normality" or whether we are already close to it. Objective: This study aims to analyze the quality of life among teachers affected by COVID-19 in Santarém, Pará, particularly focusing on symptoms that might affect their health perception. Materials and Methods: Following approval from the Human Research Ethics Committee, a descriptive, exploratory, quantitative, and cross-sectional study was conducted. Participants included teachers who completed a semi-structured questionnaire regarding their illness history, vaccination status, and current symptoms, followed by the EQ-5D-5L and WHOQOL-bref quality of life assessments. Results and Discussion: The sample comprised 20 teachers, predominantly female (80%). Although most teachers described their quality of life as "good," they reported continuous symptoms and daily medication use. The domains of pain/discomfort and anxiety/depression were most frequently noted. Commonly reported symptoms included changes in sleep patterns, lack of attention, anxiety, fatigue, memory alterations, and headaches. The study identified correlations between post-illness symptoms and daily medication use, difficulties in concentration, energy deficits, and sleep disturbances. Furthermore, an association was observed between perceived quality of life and symptoms of fatigue and attention deficits.
Keywords: COVID-19; Qualidade de vida; Professores; CNPQ::CIÊNCIAS SOCIAIS APLICADAS; Biodiversidade, Saúde e Sustentabilidade.